Cold Central Plant Recycled Asphalt Pavements in High Traffic Applications. Issue 40 (December 2018) - Timm, David H.; Diefenderfer, Brian K.; Bowers, Benjamin F.
Cold central plant recycling (CCPR) is gaining wider use in the U.S. for rehabilitating existing asphalt pavements or for new construction. Although it is used widely in lower traffic volume situations, CCPR use in high volume pavements remains an open question when considering its structural capacity and expected performance. A project completed in 2011 on I-81 in Virginia indicated CCPR may be suitable for high-volume traffic applications and was further evaluated with the construction of three CCPR test sections at the National Center for Asphalt Technology Test Track in 2012. These sections are now approaching 20 million equivalent single axle load applications and this paper documents their structural and surface performance thus far. The structural characterization indicates healthy pavements with no significant increases in measured pavement response or decreases in backcalculated moduli over time. Performance has been excellent with no cracking observed on any section, rut depths less than 0.3 inches and ride quality that has remained almost unchanged. Perpetual pavement analyses were also conducted and found that the section with a cement-stabilized base layer supporting the CCPR layer met the criteria and is likely perpetual. The other two sections, without the cement-stabilized base, did not meet the criteria and may develop bottom-up cracking. Data from the I-81 and Test Track sections enabled the Virginia Department of Transport (VDOT) to proceed with a design-build project on I-64 that will feature CCPR with a cement-stabilized base and full-depth reclamation (FDR). It is estimated that nearly 170, 000 tons of reclaimed asphalt pavement will be used with over $10 million in savings.